De novo sequencing and SNP discovery in the Scandinavian brown bear (Ursus arctos) - Norman, Anita J (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2011)
Development of molecular markers that are well-suited for use in studies on wildlife dispersal can greatly enhance conservation efforts of species affected by climate change and human-induced landscape alterations. Single nucleotide polymorphisms (SNPs) are a promising marker for such studies; however, development of SNPs in non-model species with limited or no sequence data can be challenging. This study addresses these challenges in a unique way. Reduced representation libraries (RRL) of ten individual brown bears representing the geographic range in Sweden were high-throughput sequenced on one lane of the Illumina HiSeq2000, yielding reads 100 bases in length. These reads were filtered and processed following two methods: assembly using ABySS and alignment using Stacks. Putative SNPs were then called. The alignment-only method using Stacks was not only simpler and more efficient, it also utilized 4X more reads and yielded 30X more SNPs than the assembly method. The putative SNPs showed a clear haplotype pattern that distinguished the two known lineages of brown bear in Sweden. The outcome of this study is a good start for further work in the development of a SNP-based dispersal model with the brown bear as the model species.